Are Female Political Leaders Role Models? Lessons from Asia. (June 2018) - Liu, Shan-Jan Sarah
Despite vast research on women's descriptive representation, little is known about its influence on women's political engagement in East and Southeast Asia where gender norms are different from those in other parts of the world. I theorize that the discrepancy between women's political and social rights in the region makes it difficult for women to envision themselves as equal to their male counterparts. Thus, women are less reluctant to play a "man's game" even when they see female political leaders. Using a multilevel model with data from the Asian Barometer Survey and various additional sources, I examine the impact of female parliamentarians in the region and find that they significantly reduce women's political participation. My results suggest that the female legislators' role model effect found in existing literature on Western democracies does not apply to East and Southeast Asia. Instead, female political leaders generate a backlash effect on women's political engagement. This research raises implications for the role of context in the effectiveness of women's symbolic representation and calls for further exploration on the connection between women's symbolic and descriptive representation.